Feasibility Analysis of Rice Farming by Dewi Sri Farmer Group, Bohar Village, Taman District, Sidoarjo Regency - Hamidah Hendrarini; Teguh Soedarto; Risqi Firdaus Setiawan (Future Science, 2023)
Farming cannot be separated from the receipt, income, and profits of farming. The existence of acceptance, income, and farming profits is used as an indicator of the feasibility of farming. This study aimed to determine the feasibility of rice farming of the Dwi Sri Farmer Group in Bohar Village, Taman District, Sidoarjo Regency. This research method uses a sampling method of Dewi Sri Farmer Group members. Determination of the number of samples, as many as 29 people from a total population of 40 people, is calculated by the Slovin method with an error rate of 10%. The results showed that (1) the R/C ratio of rice farming of the Dewi Sri Farmers Group was 1.7, meaning that the farming was feasible, (2) the BEP of the rice farming revenue of the Dewi Sri Farmers Group was Rp. 3,850,040 and less than the income, meaning that farming was feasible. Carried out, (3) BEP production of rice farming of the Dewi Sri Farmers Group is 1,042.7 kg and less than the total production means that the farming is feasible to run, (4) BEP of the price of rice farming of the Dewi Sri Farmers Group is Rp. 3,056, and less than the product's price means the business is worth running.